2018
DOI: 10.18632/oncotarget.25052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CB2 and TRPV1 receptors’ stimulation in pediatric acute T-lymphoblastic leukemia

Abstract: T-Acute Lymphoblastic Leukemia (T-ALL) is less frequent than B-ALL, but it has poorer outcome. For this reason new therapeutic approaches are needed to treat this malignancy.The Endocannabinoid/Endovanilloid (EC/EV) system has been proposed as possible target to treat several malignancies, including lymphoblastic diseases. The EC/EV system is composed of two G-Protein Coupled Receptors (CB1 and CB2), the Transient Potential Vanilloid 1 (TRPV1) channel, their endogenous and exogenous ligands and enzymes. CB1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(45 reference statements)
2
20
0
Order By: Relevance
“…Leukemias account for 30% of all pediatric cancers, and acute lymphoblastic leukemia (ALL) is the most prevalent pediatric leukemia, representing 75% of all pediatric leukemia cases (Terwilliger and Abdul-Hay, 2017). Punzo et al (2018a) showed that JWH133 promoted apoptosis in patients with T-ALL and a Jurkat cell line via enhanced caspase-3 expression and Bax/Bcl-2 ratio. Moreover, JWH133 prevented tumor cell growth and survival via reduced expression of AKT, ERK, and Notch-1, while increasing the expression of PTEN and p53.…”
Section: Leukemiamentioning
confidence: 99%
“…Leukemias account for 30% of all pediatric cancers, and acute lymphoblastic leukemia (ALL) is the most prevalent pediatric leukemia, representing 75% of all pediatric leukemia cases (Terwilliger and Abdul-Hay, 2017). Punzo et al (2018a) showed that JWH133 promoted apoptosis in patients with T-ALL and a Jurkat cell line via enhanced caspase-3 expression and Bax/Bcl-2 ratio. Moreover, JWH133 prevented tumor cell growth and survival via reduced expression of AKT, ERK, and Notch-1, while increasing the expression of PTEN and p53.…”
Section: Leukemiamentioning
confidence: 99%
“…The activation of TRPV1 channels by resiniferatoxin (RTX), a potent analogue of CPS and a TRPV agonist, at 5 µM, arrests the cell cycle at G0/G1 phase, reduces cell proliferation, and induces apoptosis in both Jurkat cells and cellderived T-ALL patients. In particular, after 6-12 h of treatment, a reduction of AKT, ERK, Notch-1, CDK2, and phospho-CDK2 protein levels, together with PTEN and p53 proteins upregulation in RTX-treated cells, has been reported [37]. Supporting data about the antioncogenic activity of TRPV1 were disclosed by Cetintas et al In this study, CPS inhibits the proliferation of CCRF-CEM cells in a dose-dependent manner, inducing apoptosis via caspase-3 activation and reduction of Bcl-2 expression.…”
Section: Trp Channels In Allmentioning
confidence: 95%
“…For instance, the TRPC3 channel blocker, Pyr3, enhances apoptosis induced by dexamethasone in ALL cells isolated from patients by altering calcium signalling, mitochondrial membrane potential, and ROS production [44]. In addition, the activation of TRPV1, by using the specific agonist RTX, reduced cell proliferation, blocked cell cycle, and increased apoptosis in T cells from ALL patients [37].…”
Section: Trps As Promising Diagnostic Prognostic and Therapeutic Markmentioning
confidence: 99%
“…T-ALL is caused by the diffuse bone marrow infiltration of immature T lymphoblasts, which clinically manifests as central nervous system infiltration and mediastinal mass with pleural effusion in the early stage (6). T-ALL is far more difficult to treat than B-ALL and has a poor long-term prognosis (7,8) resulting from poor sensitivity and resistance to chemotherapeutic drugs, issues with remission and clearance of bone marrow microresidual lesions, and a high recurrence rate in the central nervous system (9,10). With the advancement of chemotherapy regimens, the 5-year disease-free survival rate of pediatric T-ALL has substantially improved (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%